2013
DOI: 10.4028/www.scientific.net/amr.746.489
|View full text |Cite
|
Sign up to set email alerts
|

Application of Several Kinds of Clays and a New Type of Nano-Modified Bontonite in Drilling Fluids

Abstract: Six kinds of materials, including two types of nanoclays, were added into drilling fluids for being substitutes of common bentonite. Swelling properties and yield of these clays were determined. Rheology, filtration property and properties at high temperature of drilling fluids prepared by the six kinds of clays respectly were also evaluated in laboratory. The results indicate that the nanobentonite modified by intercalated polymerization can improve various properties of drilling fluids. Besides, sepiolites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In oil and gas well drilling, applications of smart fluids have been widely focused on the dispersion of nanoparticles in base drilling fluids with the aim of enhancing drilling fluid properties [11][12][13]. In smart nanoparticle drilling fluids, nanoparticles have been known to influence drilling fluid performances due to changes in wt.% concentrations, higher specific surface area, and high quantum activity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oil and gas well drilling, applications of smart fluids have been widely focused on the dispersion of nanoparticles in base drilling fluids with the aim of enhancing drilling fluid properties [11][12][13]. In smart nanoparticle drilling fluids, nanoparticles have been known to influence drilling fluid performances due to changes in wt.% concentrations, higher specific surface area, and high quantum activity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…When considering the effects of nanoparticles on wellbore stability, it is suggested that, due to their tiny particle sizes, they are able to invade and plug shale nanoporous media, thereby enhancing the mechanical strength of unconsolidated shale formations and thus improving wellbore stability [17,18]. On the influence of nanoparticles on water-based drilling fluids, since bentonite clay surfaces are considered to be net negatively charged with clouds of cations due to electron deficiency owing to isomorphic substitution in their unit layer, functionalized and charged nanoparticles (cationic and anionic) can cause either an increase or decrease in drilling fluid rheological properties through electrostatic attractive and repulsive forces [13]. It is suggested that this electrostatic interaction can equally result in an increase or decrease in fluid loss volumes by drilling fluid systems, hence making research on smart drilling fluids an area of importance when considering meeting technical challenges during oil and gas well drilling operations.…”
Section: Introductionmentioning
confidence: 99%